2023
DOI: 10.1093/ehjopen/oead026
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes of atrial fibrillation ablation in heart failure patients with and without cardiac amyloidosis: a Nationwide Readmissions Database analysis (2015–2019)

Abstract: Atrial fibrillation (AF) in patients with cardiac amyloidosis (CA) has been linked with a worse prognosis. The current study aimed to determine the outcomes of AF catheter ablation in patients with CA. The National Readmission Database (NRD) 2015-2019 was used to identify patients with AF and concomitant heart failure (HF). Among these, patients who underwent catheter ablation were classified into two groups, patients with and without CA. The adjusted odds ratio (aOR) of index-admission and 30-day readmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Using a nationwide database, Ullah et al . 1 demonstrated that AF ablation in patients with cardiac amyloidosis was associated with higher in-hospital all-cause mortality and net adverse clinical events both during the index hospitalization and at 30-day follow-up as compared with background-matched heart failure patients without cardiac amyloidosis. Several concerns are raised.…”
mentioning
confidence: 97%
“…Using a nationwide database, Ullah et al . 1 demonstrated that AF ablation in patients with cardiac amyloidosis was associated with higher in-hospital all-cause mortality and net adverse clinical events both during the index hospitalization and at 30-day follow-up as compared with background-matched heart failure patients without cardiac amyloidosis. Several concerns are raised.…”
mentioning
confidence: 97%
“… 6 In their study, Ullah et al . 5 report no significant difference in the odds of stroke, cardiac tamponade, and major bleeding between the two groups, but the respective rate of fatal events for each specific category of adverse events is unknown. After AF ablation, the vast majority of deaths from periprocedural complications occur (with the exception of atrio-oesophageal fistula) within a few days of the procedure.…”
mentioning
confidence: 97%
“…However, Ullah et al . 5 observed significantly higher all-cause mortality at both index admission [odds ratio (OR = 9.03)] and 30-day readmission (OR = 4.28) in patients with CA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Valvular Heart Disease , EHJ Open presented a State-of-the-Art review on the association of CA with aortic stenosis, from pathophysiology to treatment. 18 Furthermore, in Arrhythmia & Electrophysiology , Ullah et al used nationwide health data to conclude that atrial fibrillation ablation was associated with significantly higher net adverse clinical events in patients with CA, 19 albeit atrial fibrillation catheter ablation remains effective to maintain sinus rhythm in patients with CA. 20 Finally, novel findings on Vascular & Cardiac Imaging of CA include a suggested novel echocardiographic risk score 21 and CA prognostic prediction by cardiac magnetic resonance imaging (cMRI).…”
mentioning
confidence: 99%